2008
DOI: 10.1007/s11172-008-0317-z
|View full text |Cite
|
Sign up to set email alerts
|

Cation mobility in systems based on high-molecular-weight sulfonic acids and polyaniline

Abstract: Conduction properties and intermolecular interactions in systems based on high mole cular weight sulfonic acids (poly(4 styrenesulfonic), poly(2 acrylamidomethylpropane sulfonic), and perfluorosulfonic (MF 4SC)) and polyaniline were studied by impedance and IR spectroscopy. In all systems, an interpolyelectrolyte complex is formed due to strong hydrogen bonding. In two former cases, the interpolyelectrolyte complexes form nanodispersed powders with ionic and electronic conductivity. MF 4SC-polyaniline solu tio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…7. 17 When these results are compared with the data obtained for the membranes containing PAni and acid, 8 a low electron component of conductivity can be noted as a characteristic feature of the composite membranes pre pared in our group. It is most probable that this is due to the fact that the polyaniline fragments are isolated from each other by the matrix of the membrane.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…7. 17 When these results are compared with the data obtained for the membranes containing PAni and acid, 8 a low electron component of conductivity can be noted as a characteristic feature of the composite membranes pre pared in our group. It is most probable that this is due to the fact that the polyaniline fragments are isolated from each other by the matrix of the membrane.…”
Section: Resultsmentioning
confidence: 54%
“…17, 26 The surface of the latter is not hydrophobic because of the presence of nitrogen atoms, but these are the nitrogen atoms that form strong hydro gen bonds with the sulfo groups upon incorporation into MF 4SC. 17 Thus, the hydrophilic sites block each other in the system considered. According to the thermo gravimetry data, this noticeably decreases the humidity of the membranes if PAni is incorporated in them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second method consisted in casting of composite membranes from solution of polymer and precursor for further particle synthesis. 10,11 This method provided incorporation of SiO 2 up to 13.5 vol% (15 wt%) and PAni up to 26 vol% (14 wt%). The transmission electron microscopy showed that in all cases isolated nanoparticles (2-6 nm) were formed in membrane matrix.…”
mentioning
confidence: 99%